TINDAK TUTUR DIREKTIF ANTARA DOSEN DAN NAHASISWA DALAM PERKULIAHAN MATA KULIAH BAHASA INDONESIA DI UMI - ihram sari; Umar Mansyur (Balai Bahasa Sulawesi Tengah, 2019)
The writer is interested in examining directive discourse between lecture and studentsin indonesian learning process as general subject in indonesia muslim university. The problem statement of this research is how the politeness forms from lecturer to students, students to lecturer, and students to students in Indonesian Language Subject at Universitas Muslim Indonesia. The purpose of this study is to describe the form of politeness in the interaction of lecturers to students, students to lecturers, and students to students. This study focused on lecturers who teach general Indonesian language subject at the Faculty of Letters and first semester students, especially those who program general subject in Indonesian. The collected data will be analyzed using qualitative descriptive analysis techniques. Based on the results of the research found, forms of language politeness in the interaction of lecturers to students in the form of declarative sentences,namely obeying the maxim of wisdom, praise, and agreement; interrogative sentences, namely obeying the maxim of wisdom; imperative sentence, namely obeying the maxim of wisdom; the exclamation sentence, namely obeying the maxim of wisdom; and language politeness in the interaction of students to lecturers in the form of declarative sentences, namely obeying the maxim of generosity and agreement; interrogative sentences, namely obeying the maxim of generosity; the exclamation sentence, namely obeying the maxim of wisdom; and the form of politeness in the interaction of students to students in the form of declarative sentences, namely the maxim of wisdom, generosity, agreement and sympathy; interrogative sentences, namely the maxim of wisdom and sympathy; imperative sentence, namely the maxim of wisdom; exclamation sentence, namely the maxim of wisdom. Based on the results of the study it can be concluded that the use of politeness in the formal setting is very useful for people's lives, including in the education side.